Isolation of Nocardia mexicana from focal proliferative tenosynovitis and arthritis in a steer. Issue 5 (May 2015) - Owen, H; Buckle, K; Olm, J; Leitner, M; Pandey, S; Gaughan, JB; Sullivan, ML; Lees, AM; Gibson, JS
<x xml:space="preserve">Abstract</x> Case report An 18‐month‐old Charolais steer was presented with lameness and fluctuant swelling of the right stifle joint, which yielded neutrophils on fine‐needle aspiration. A diagnosis of bacterial proliferative tenosynovitis and arthritis was made on postmortem and histological examination. Culture and 16S rRNA sequencing identified a Nocardia sp. with 99% homology with the corresponding DNA fragment of N. mexicana DSM 44952. Antimicrobial susceptibility testing revealed the isolate was susceptible to co‐trimoxazole and third‐generation cephalosporins. Conclusion We report the first case, both in Australia and internationally, of proliferative tenosynovitis and arthritis caused by Nocardia spp. infection in a bovine and the first report of pathology attributed to N. mexicana in a veterinary patient. Given the limited susceptibility of the bacteria, the poor antimicrobial penetration that would be expected and the morphological changes that had taken place in the joint; the steer would have required protracted antimicrobial treatment in addition to invasive debridement of the lesion. This case emphasises the importance of routinely performing cytology and extended incubation of cultures in cases of arthritis in order to make ethical and economically viable treatment decisions.